Motion of spinning particles around electrically charged black hole in Eddington-inspired Born–Infeld gravity - Yang, Ke; Gu, Bao-Min; Zhang, Yu-Peng (The European physical journal. C, Particles and fields, 2022)
A test particle possessing spin angular momentum moves along a non-geodesic path due to an additional spin-curvature force. We study the spinning test particle moving in the vicinity of the electrically charged black hole formation in Eddington-inspired Born–Infeld (EiBI) gravity. Through the numerical analysis of its effective potential and orbits, it is found that the orbital eccentricity reduces as the deviation parameter κ increases. By comparing the orbits for the observed stars around Sagittarius A*, we conclude that the observed orbits with too large radii can not give a stringent constraint with acceptable magnitude. To dig out the potential observation effects of the relations between the orbits and parameter κ , we mainly focus on the orbits in the vicinity of black hole in this paper. The parameters of inner most stable circular orbit (ISCO) decrease monotonously with κ when the spin angular momentum is small, however they change non-monotonously with κ when the spin is large enough. Moreover, the spin dependences of ISCO parameters have similar behavior to that of Reissner–Nordström (RN) black hole. We analyze the causality of the circular orbits by using the superluminal constraint condition as well. As a result, two new parameter regions may emerge in case of large κ , where the particle has two stable circular orbits with one subluminal and the other superluminal.